1988
DOI: 10.1080/00039896.1988.10545954
|View full text |Cite
|
Sign up to set email alerts
|

The Total Human Environmental Exposure Study (THEES) to Benzo(a)pyrene: Comparison of the Inhalation and Food Pathways

Abstract: The assessment of human exposure to an environmental contaminant requires the measurement of levels present in each pathway of possible contact. In this paper, the design considerations and Phase I results of a human exposure study focused on Benzo(a)pyrene (BaP) are discussed. This study site, located in Phillipsburg, New Jersey, is a city that contains a metal pipe foundry, which is a suspected major source of BaP. Three outdoor PM-10 samplers (used to collect BaP-containing particles with an aerodynamic siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(70 citation statements)
references
References 10 publications
2
66
0
2
Order By: Relevance
“…Several studies have indeed shown that the intake of PAHs via the diet is large (Beckman Sundh et al 1998;de Vos et al 1990) and much higher than the intake via inhalation (Lioy et al 1988;Lodovici et al 1995;Vaessen et al 1988;WHO/IPCS 1998). Data on the origin of PAHs in food are limited; however, it has been suggested that the major part originates from precipitated particulate material (de Vos et al 1990;Lodovici et al 1995).…”
Section: Pah Exposure In Humansmentioning
confidence: 99%
“…Several studies have indeed shown that the intake of PAHs via the diet is large (Beckman Sundh et al 1998;de Vos et al 1990) and much higher than the intake via inhalation (Lioy et al 1988;Lodovici et al 1995;Vaessen et al 1988;WHO/IPCS 1998). Data on the origin of PAHs in food are limited; however, it has been suggested that the major part originates from precipitated particulate material (de Vos et al 1990;Lodovici et al 1995).…”
Section: Pah Exposure In Humansmentioning
confidence: 99%
“…Humans may be exposed to these compounds from a wide variety of sources, including occupation (coke oven or iron foundry workers), environment (air pollutants, drinking water), personal habits (e.g., smoking), medical treatment (coal tar), and diet (broiled and smoked foods) (1)(2)(3)(4)(5)(6)(7)(8). PAHs are readily absorbed into the body through the skin, lungs, and gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Only 2.5% of intake is attributable to inhalation, and even less to drinking water consumption, non-dietary ingestion, and dermal contact with contaminated soil (EPA, 2001a). Measured concentrations in foods also reveal that dietary intake can be significantly greater than inhalation for PAHs (Lioy et al, 1988;Butler et al, 1993;Chuang et al, 1999;Wilson et al, 2001). …”
Section: Introductionmentioning
confidence: 99%